2008
DOI: 10.1111/j.1529-8817.2008.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

THE UTILITY OF PROTEOMICS IN ALGAL TAXONOMY: BOSTRYCHIA RADICANS/B. MORITZIANA (RHODOMELACEAE, RHODOPHYTA) AS A MODEL STUDY1

Abstract: A comparison of the proteome of eight genetically well-characterized isolates of the Bostrychia radicans (Mont.) Mont./B. moritziana (Sond. ex Kütz.) J. Agardh species complex was undertaken to establish if genetic relationships among them can be determined using proteome data. Genetic distances were calculated on the basis of common and distinct spots in two-dimensional gel electrophoresis (2-DE). Proteomes of the male and female plants of each population were compared to analyze the range of genetic differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Although these glycoproteins must be important for fertilization, which can be blocked by adding the complimentary sugars or lectins, it is still uncertain whether these glycoproteins are responsible for species recognition. Quite recently, Kim et al (2008) undertook a comparison of the proteome among eight isolates of the Bostrychia radicans/moritziana species complex showing various reproductive reactions with each other. The male and female isolates had 3.7-7.1% sex-specific proteins, and the lack of any shared sex-specific proteins across all isolates may suggest rapid evolution of these proteins (Kim et al, 2008).…”
Section: Biochemical Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these glycoproteins must be important for fertilization, which can be blocked by adding the complimentary sugars or lectins, it is still uncertain whether these glycoproteins are responsible for species recognition. Quite recently, Kim et al (2008) undertook a comparison of the proteome among eight isolates of the Bostrychia radicans/moritziana species complex showing various reproductive reactions with each other. The male and female isolates had 3.7-7.1% sex-specific proteins, and the lack of any shared sex-specific proteins across all isolates may suggest rapid evolution of these proteins (Kim et al, 2008).…”
Section: Biochemical Isolationmentioning
confidence: 99%
“…Quite recently, Kim et al (2008) undertook a comparison of the proteome among eight isolates of the Bostrychia radicans/moritziana species complex showing various reproductive reactions with each other. The male and female isolates had 3.7-7.1% sex-specific proteins, and the lack of any shared sex-specific proteins across all isolates may suggest rapid evolution of these proteins (Kim et al, 2008). Such a proteome analysis is expected to become an important cue for the elucidation of the molecular mechanisms of sex as well as species recognition in red algae.…”
Section: Biochemical Isolationmentioning
confidence: 99%
“…Bostrychia radicans / B. moritziana (Plantae, Rhodophyta) (Kim et al, 2008). The figure correspond to B. moritziana.…”
Section: Appendix B: Macroalgae Methodologymentioning
confidence: 99%
“…In another important proteomic work with macroalgae developed by Kim et al (2008) and published contemporarily with the Contreras et al (2008) work, using as models the red algae Bostrychia radicans and B. moritziana (Plantae, Rhodophyta), used a lysis buffer comprised principally by urea and thiourea (detailed protocol in Appendix B). Although these species belong to the same group of red algae like G. changii, the simplicity of this method utilized in comparison with the phenol one (Wong et al, 2006) is due to the morphological characteristics of this species (see image in Appendix B).…”
Section: Macroalgae Methodologymentioning
confidence: 99%
“…1,3 Moreover, these species have received considerable molecular attention, leading to insights into its evolution, and nomenclatural revision. 4,5 Concerning the chemical composition of Bostrychia species, previous studies have only reported the occurrence and chemotaxonomic implications of its polyols and low-molecular-mass carbohydrates. [6][7][8][9] In this context, polysaccharides isolated from Bostrychia montagnei Harvey were characterized 10 while the antiherpetic and anticoagulant activities of these compounds were reported by Duarte. 11 Moreover, two aromatic compounds were isolated from the alga Bostrychia tenella, namely, the new sulfated metabolite potassium 4-(hydroxymethyl)-benzenesulfonate and the compound 1-methoxyphenethyl alcohol.…”
Section: Introductionmentioning
confidence: 99%